Nasal cavity hemostasis filling material as well as preparation method and application thereof
Through the composite materials of ε-polylysine carbon dots, recombinant humanized collagen and carboxylated polyvinyl alcohol copolymer, the problems of poor antibacterial properties and insufficient mechanical strength of nasal hemostasis materials are solved, and effective nasal hemostasis is achieved and wound healing, reducing the risk of infection.
Patent Information
- Application Number
- CN202411344139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
Existing nasal hemostatic materials have problems such as poor antibacterial performance, poor comfort, chemical residues and insufficient mechanical strength, making it difficult to effectively stop bleeding and promote wound healing, and there is a risk of reinfection.
Composite materials formed by copolymers of ε-polylysine carbon dots (PL-CDs)/recombinant humanized collagen (RHC) and ε-polylysine (PL), carboxylated polyvinyl alcohol (CPVA) , through electrostatic action and hydrogen bonding, nasal hemostasis filling materials with antibacterial, adjustable mechanical properties and rapid degradation were prepared.
Effective nasal hemostasis, rapid wound healing, antibacterial performance and comfort improvements are achieved, reducing the risk of reinfection and avoiding secondary damage during material removal.
Smart Images

Figure CN119185633A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical biomaterials, and in particular relates to a nasal hemostatic filling material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In recent years, the incidence of nasal diseases has been increasing. Among them, patients with severe sinusitis and nasal tumors need to undergo nasal endoscopy for surgery. The nasal mucosa is rich in blood vessels, and surgery can easily cause bleeding. Hemostatic sponges are usually used to fill the nasal cavity for hemostatic filling, but there are a large number of bacteria in the nasal cavity, which faces the risk of infection and infection in the lower respiratory tract after surgery; the wound heals slowly and is prone to re-infection. Clinically, degradable hemostatic filling materials represented by nano-absorbent sponges and high-expansion hemostatic filling materials represented by polyvinyl alcohol (PVA) are mainly used. The former has good elastic support and ideal self-degradation characteristics, and is easy for patients to use, but the product cannot be used as a whole and recovers slowly; the latter has a long degradation cycle, and high expansion can easily cause nasal discomfort, and secondary bleeding is easy to occur after removal. The hemostatic materials on the market are not antibacterial and are not comfortable. The pain during use is obvious and cannot bring a good experience to patients.
[0004] Patent CN 202010355177.9 discloses a nasal filling material and a preparation method thereof, which is a nasal filling material prepared by electrospinning using carboxymethyl cellulose modified with polylysine, and has good biocompatibility and is degradable, but the inventors found that its mechanical strength is poor and cannot play a good supporting role. Patent CN 202010963028.0 discloses a nasal filler for hemostasis and a preparation method thereof, which uses one or more elastic nasal filling materials of PVA, chitosan, alginate, and gelatin that are proportionally reduced according to the shape of the nasal cavity, but the shape of the prepared material is single and cannot meet the needs of different patients; Patent CN 201910509802.8 discloses a preparation method of a gelatin nasal hemostatic sponge, which prepares a nasal hemostatic sponge using PVA and gelatin sponge. The inventors found that it uses chemical cross-linking agents multiple times, and the residual cross-linking agents may induce inflammatory reactions. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a nasal hemostatic filling material and a preparation method and application thereof. Specifically, the nasal hemostatic filling material of the present invention is a composite material formed by ε-polylysine carbon dots (PL-CDs) / recombinant humanized collagen (RHC) and ε-polylysine (PL), carboxylated polyvinyl alcohol (CPVA) copolymer. It has been verified by experiments that it has antibacterial properties and adjustable mechanical properties, can be effectively degraded in the nasal cavity, has good hemostatic properties, accelerates wound healing, and does not cause immune response. Based on the above research results, the present invention is completed.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a nasal hemostatic filling material, which is a composite material formed by ε-polylysine carbon dots (PL-CDs) / humanized collagen (RHC), ε-polylysine (PL) and carboxylated polyvinyl alcohol (CPVA) copolymer.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned nasal hemostatic filling material, the preparation method comprising:
[0009] S1, mixing the ε-polylysine carbon dot solution with the humanized collagen solution to obtain a PL-CDs / RHC mixed solution;
[0010] S2. Add EDC and NHS to the carboxylated polyvinyl alcohol copolymer solution for activation treatment, dry and redissolve, then add ε-polylysine and PL-CDs / RHC mixed solution, stir evenly for reaction, dialyze and freeze-dry to obtain the product.
[0011] The third aspect of the present invention provides the use of the above-mentioned hemostatic filling material in the preparation of nasal hemostatic filling products.
[0012] The product may be a medical device.
[0013] A fourth aspect of the present invention provides a nasal hemostatic filling product, the product comprising at least a hemostatic filling material. The nasal hemostatic filling product of the present invention can effectively prevent nasal bleeding and nasal septum hematoma by absorbing blood and exerting physical compression, while the degradation property can avoid secondary damage caused by material removal.
[0014] Beneficial technical effects of one or more of the above technical solutions:
[0015] (1) The above technical solution effectively prevents nasal bleeding and nasal septum hematoma by absorbing blood and exerting physical compression, while the degradation characteristics can avoid secondary damage caused by material removal.
[0016] (2) PVA is carboxylated to form irregular fragments, which improves its water solubility. The degradation time of the material is controlled according to the degree of carboxylation and the content of each component. PVA is easy to swell, and the cross-linking of PL and RHC with CPVA makes the expansion performance of the nasal filling material moderate, preventing PVA from over-swelling and causing nasal discomfort. At the same time, the composite material has the adhesion properties of PL, which can better fit the traumatic tissue.
[0017] (3) Significant antibacterial properties: The introduction of PL-CDs gives the composite material highly efficient antibacterial properties, avoiding wound infection, preventing descending respiratory tract infection, and reducing the use of antibiotics.
[0018] (4) Rapid hemostasis performance. The introduction of RHC enables the composite material to quickly stop bleeding, promote the repair of damaged tissue, and accelerate wound healing. Combined with PVA expansion and compression hemostasis, rapid hemostasis can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1 This is the diameter distribution diagram of PL-CDs prepared in Example 1 of the present invention.
[0021] Figure 2 This is the antibacterial diameter diagram of the product prepared in Example 1 of the present invention.
[0022] Figure 3 This is a diagram showing the antibacterial effect of products prepared in some embodiments of the present invention on Staphylococcus aureus.
[0023] Figure 4 This is a diagram showing the antibacterial effect of the product prepared in the comparative example of the present invention on Staphylococcus aureus.
[0024] Figure 5 The following are the degradation diagrams of the products prepared in various embodiments and comparative examples of the present invention.
[0025] Figure 6 The diagram is a graph of the hemostasis time of the products prepared in various embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0026] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0027] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof. It should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention.
[0028] As mentioned above, the existing reported nasal hemostatic materials have problems such as poor or no antibacterial properties, poor comfort, and chemical residues.
[0029] The ideal nasal hemostatic material should have the following characteristics: antibacterial, non-cytotoxic, non-allergenic, with certain mechanical properties, can be effectively degraded in the nasal cavity, and have good hemostatic and wound repair effects.
[0030] In view of this, the present invention provides a nasal hemostatic filling material, which is a composite material formed by ε-polylysine carbon dots (PL-CDs) / recombinant humanized collagen (RHC) and ε-polylysine (PL) and carboxylated polyvinyl alcohol (CPVA) copolymer.
[0031] Among them, PL-CDs have rich functional groups on their surface and carry positive charges. When in contact with bacteria, they interact with the negatively charged bacterial cell membrane through electrostatic interaction, interfere with the normal physiological metabolism of bacteria, destroy the integrity of their cell membranes, and then kill bacteria, playing an antibacterial role. PL-CDs and RHC are combined through hydrogen bonds, without the introduction of cross-linking agents, which is safer and has both the antibacterial properties of PL-CDs and the wound repair and hemostatic properties of RHC.
[0032] The water solubility of PVA after carboxyl modification is increased, which can accelerate degradation. EDC and NHS act as catalysts, and the carboxyl groups of CPVA react with the amino groups in PL and PL-CDs / RHC respectively to assemble into nasal hemostatic filling materials. The modified CPVA regulates the expansion and mechanical properties of the composite material. After combining with RHC, it has a strong hemostatic and trauma repair effect, which can make up for the hemostatic performance weakened by the reduction of expansion performance. The final nasal hemostatic filling material has adjustable expansion and mechanical properties, reduces the high expansion effect of CPVA, and can be antibacterial and quickly stop bleeding.
[0033] Therefore, in a typical embodiment of the present invention, a hemostatic filling material is provided, which is a composite material formed by ε-polylysine carbon dots (PL-CDs) / humanized collagen (RHC), ε-polylysine (PL) and carboxylated polyvinyl alcohol (CPVA) copolymer.
[0034] The ε-polylysine carbon dots are carbon quantum dots prepared by using ε-polylysine as a carbon source. Specifically, the preparation method is as follows: ε-polylysine is placed in a high temperature environment for pyrolysis treatment, and the carbon dots are obtained after crushing and purification.
[0035] The average molecular weight of the ε-polylysine is 1000-10000, preferably 4000;
[0036] The specific conditions of the pyrolysis treatment are: treating at 200-300°C for 0.5-5 hours, preferably treating at 240°C for 1 hour, and then keeping warm for 1-10 hours, preferably keeping warm for 3 hours;
[0037] Furthermore, the cooled pyrolysis product is soaked in water, the water-insoluble solid is separated and ground, placed in water for ultrasonic treatment, centrifuged to obtain the supernatant, the supernatant is mixed with the remaining pyrolysis product soaking water for dialysis, and then freeze-dried to obtain the product.
[0038] Wherein, the specific conditions of the dialysis are: the molecular weight cut-off is 1000-10000, preferably 3000;
[0039] The specific conditions for freeze-drying are: pre-freezing at -20°C for 24 hours, rapid freezing at -80°C for 12 hours, and freeze-drying at -20°C for 24 hours.
[0040] Furthermore, the freeze-dried product was ground in the dark to obtain positively charged ε-polylysine carbon dots with a particle size distribution of 2-10 nm and a Zeta potential of +8.62 mV.
[0041] The humanized collagen can be recombinant humanized collagen, which is combined with ε-polylysine carbon dots through hydrogen bonds without the introduction of cross-linking agents, is safer, and has both the antibacterial properties of ε-polylysine carbon dots and the wound repair and hemostatic properties of recombinant humanized collagen.
[0042] Furthermore, the recombinant humanized collagen may be the recombinant humanized collagen developed by Shandong Junxiu Biotechnology Co., Ltd., which has been disclosed in Chinese Patent Publication No. CN 118255869A.
[0043] The carboxylated polyvinyl alcohol copolymer is prepared by the following method:
[0044] Vinyl acetate is added to methanol, and under inert gas conditions, azobisisobutyronitrile and acrylic acid are added to carry out copolymerization reaction to obtain the intermediate product P(VAc-co-AA); then P(VAc-co-AA) is redissolved in methanol, and sodium hydroxide methanol solution is added to carry out alcoholysis to obtain a gel-like product, which is purified to obtain CPVA.
[0045] Wherein, the inert gas may be nitrogen;
[0046] The mass ratio of vinyl acetate, azobisisobutyronitrile and acrylic acid is 10-20:001-0.1:0.1-1, preferably 18:0.03:0.063. The specific conditions of the copolymerization reaction are: reacting at 50-80° C. for 1-20 hours, preferably at 65° C. for 8 hours.
[0047] In another specific embodiment of the present invention, a method for preparing the above-mentioned nasal hemostatic filling material is provided, and the preparation method comprises:
[0048] S1, mixing the ε-polylysine carbon dot solution with the humanized collagen solution to obtain a PL-CDs / RHC mixed solution;
[0049] S2. Add EDC and NHS to the carboxylated polyvinyl alcohol copolymer CPVA solution for activation treatment, dry and redissolve, then add ε-polylysine and PL-CDs / RHC mixed solution, stir evenly for reaction, dialyze and freeze-dry to obtain the product.
[0050] Wherein, in step S1, the mass fraction of the ε-polylysine carbon dot solution is 5-15% (w / v), preferably 10%, and the solvent can be water, further purified water.
[0051] The mass fraction of the humanized collagen solution is 1-5% (w / v), preferably 3%.
[0052] In the step S2, the mass fraction of the carboxylated polyvinyl alcohol copolymer solution is 1-10% (w / v), preferably 5%, and the solvent of the carboxylated polyvinyl alcohol copolymer solution is anhydrous ethanol or dichloromethane.
[0053] The molar ratio of CPVA to EDC and NHS is 5-20:0.5-5:0.1-1, preferably 10:1:0.5;
[0054] The specific conditions for drying and re-dissolving are: drying at 50-70°C (preferably 60°C) to precipitate solids, and then adding water (preferably purified water) for re-dissolving; the mass volume ratio of the carboxylated polyvinyl alcohol copolymer to water is 0.5-2:15-25 (g / mL), further 1:20.
[0055] The mass ratio of PL-CDs / RHC:CPVA:PL is 1-10:0.5-2:0.5-2, further preferably 2-6:1:1, and further preferably 4:1:1.
[0056] The specific reaction conditions are: react at 20-40°C for 1-20h, preferably at 30°C for 8h.
[0057] In another specific embodiment of the present invention, there is provided use of the above-mentioned hemostatic filling material in the preparation of a nasal hemostatic filling product.
[0058] The product may be a medical device.
[0059] In another specific embodiment of the present invention, a nasal hemostatic filling product is provided, the product at least comprising a hemostatic filling material. The nasal hemostatic filling product of the present invention can effectively prevent nasal bleeding and nasal septum hematoma by absorbing blood and exerting physical compression, and the degradation property can avoid secondary damage caused by material removal.
[0060] In another specific embodiment of the present invention, the product may be a medical device.
[0061] In another specific embodiment of the present invention, when the product is a medical device, it can be a drug-device combination product, which refers to a product composed of a drug and a medical device and produced as a single entity. A specific embodiment of the drug-device combination product can be the above-mentioned nasal hemostatic filling material, which can obviously be used as a gel sponge dressing medical device.
[0062] In another specific embodiment of the present invention, the drug may further include at least one non-drug active ingredient, and the non-drug active ingredient may include a pharmaceutically acceptable excipient, carrier, etc., which is not specifically limited herein.
[0063] The present invention is further explained by the following examples, but they are not intended to limit the present invention. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0064] Example 1
[0065] 1. Preparation of PL-CDs
[0066] 10 g of PL with an average molecular weight of 4000 was placed in a crucible and pyrolyzed at 240°C for 1 hour, kept at the pyrolysis temperature for 3 hours, and naturally cooled to room temperature. The cooled pyrolysis product was immersed in 20 mL of deionized water, and the water-insoluble solid was separated and ground into powder, which was placed in 20 mL of deionized water, ultrasonicated for 6 minutes and stopped for 3 minutes, cycled 5 times, centrifuged at 8000 rad / min, and the supernatant was taken. It was mixed with the above 20 mL solution directly dissolved in deionized water and dialyzed for 36 hours (molecular weight cutoff was 3000). The dialyzed product was further freeze-dried, specifically: pre-freezing at -20°C for 24 hours, rapid freezing at -80°C for 12 hours, freeze-drying at -20°C for 24 hours, and grinding in the dark to obtain positively charged PL-CDs with a particle size distribution of 2-10 nm and a Zeta potential of +8.62 mV.
[0067] 2. Preparation of CPVA
[0068] 18g of vinyl acetate (VAc) was added to a flask containing 50mL of methanol, nitrogen was introduced at room temperature for 30min, and then 0.03g of azobisisobutyronitrile and 0.63g of acrylic acid (AA) were added, and the reaction time was 65°C for 8 hours. After the reaction, the obtained product was precipitated in deionized water, filtered and dried to obtain the intermediate product P(VAc-co-AA). Then 10g of P(VAc-co-AA) was redissolved in 30mL of methanol, and 5mL of 1mol / L sodium hydroxide methanol solution was added, and alcoholyzed in a water bath at 50°C for 30min to obtain a gel product, which was then redissolved in deionized water, filtered to remove impurities, and finally precipitated in methanol. After filtering and drying, CPVA was obtained, and the carboxyl content was measured to be 10.2%.
[0069] 3. Preparation of Nasal Hemostatic Packaging Materials
[0070] The present invention uses RHC (recombinant human type III collagen prepared in Example 1 of CN 118255869A) developed by Shandong Junxiu Biotechnology Co., Ltd. RHC is dissolved in purified water to prepare a 3% (w / v) RHC solution, and the prepared PL-CDs is dissolved in purified water to prepare a 10% (w / v) PL-CDs solution, and the two are mixed to obtain a PL-CDs / RHC mixed solution, and the volume ratio of the RHC solution to the PL-CDs solution is 10:1.
[0071] Take 10g of the prepared CPVA above and add it to a round-bottom flask containing 200mL of anhydrous ethanol to dissolve at 50°C, then cool to 30°C, transfer to a beaker, add EDC and NHS (molar ratio of 2:1) for activation for 2h, dry by rotary evaporation at 60°C, and dissolve in 200mL of purified water again. Add 10g of PL powder (average molecular weight 4000) and 30°C preheated PL-CDs / RHC mixed solution, the solute mass ratio of PL-CDs / RHC:CPVA:PL is 4:1:1, stir evenly, react at 30°C for 8h, dialyze in PBS buffer for 48h (molecular weight cutoff 3000), and freeze-dry (pre-freeze at -20°C for 18h, freeze-dry at -40°C for 36h) to obtain a sponge in which the molar ratio of CPVA to EDC is 10:1, and a nasal hemostatic filling material is obtained.
[0072] Example 2: The preparation method is the same as that of Example 1, except that the mass ratio of VAc to AA is 100:4.
[0073] Example 3: The preparation method is the same as that of Example 1, except that the mass ratio of VAc to AA is 100:0.8.
[0074] Example 4: The preparation method is the same as that of Example 1, except that the volume ratio of the RHC solution to the PL-CDs solution is 15:1.
[0075] Example 5: The preparation method is the same as that of Example 1, except that the mass ratio of PL-CDs / RHC:CPVA:PL solutes is 4:0.8:1.
[0076] Comparative Example
[0077] Comparative Example 1: The preparation method is the same as that of Example 1, except that PL-CDs is not added.
[0078] Comparative Example 2: The preparation method is the same as that of Example 1, except that the concentration of PL-CDs added is 5%, and the volume ratio of the RHC solution to the PL-CDs solution is 10:1.
[0079] Comparative Example 3: The preparation method is the same as that of Example 1, except that the mass ratio of VAc to AA is 100:0.5.
[0080] Comparative Example 4: The preparation method is the same as that of Example 1, and the only difference from Example 1 is that the mass ratio of PL-CDs / RHC, CPVA and PL is 4:1:3.
[0081] Comparative Example 5: The preparation method is the same as that of Example 1, except that the volume ratio of the RHC solution to the PL-CDs solution is 6:1.
[0082] Comparative Example 6: The preparation method is the same as that of Example 1, except that the solute mass ratio of PL-CDs / RHC, CPVA and PL is 7:1:1.
[0083] Experimental verification part
[0084] (1) Cytotoxicity experiments prove biocompatibility
[0085] The MTT method was used to test the in vitro cytotoxicity. The prepared nasal hemostatic filling material samples were cut into small pieces of about 1 mm in length. After ultraviolet sterilization, 1640 culture medium containing 10% calf serum was used as the extraction medium under sterile conditions. The concentration of the extraction stock solution was 0.1 g / mL. The extraction was performed at 37°C for 24 hours to obtain the extract. The extract was then added to the wells of a 96-well cell culture plate inoculated with L929 fibroblasts. After culturing at 37°C and 5% CO2 for 24 hours, the absorbance was measured on the same day, and the survival rate (%) was calculated, namely:
[0086] Survival rate (%) = OD 570e / OD 570b ×100%
[0087] Where: OD 570e -Absorbance of each test group;
[0088] OD 570b -Absorbance of medium control group.
[0089] MTT results: The cell survival rates of each group are shown in Table 1. The survival rates of the experimental groups were all higher than 90%, indicating that the prepared nasal hemostatic filling material is safe, non-toxic and has good biocompatibility.
[0090] (2) In vitro degradation experiment
[0091] Eleven samples of the stents of Examples 1-5 and Comparative Examples 1-6 were placed in reagent bottles containing simulated body fluid (SBF solution) and their degradation was observed at 3d / 5d / 7d to calculate the mass loss rate. Mass loss rate (%) = (m1-m2) / m1×100%, where m1 is the initial test mass and m2 is the mass after degradation time t.
[0092] In Example 1, Example 2, Example 3, and Comparative Example 3, as the mass ratio of VAc to acrylic acid increases, the degree of carboxylation increases, and the mass loss rate at the same time point is high ( Figure 5 ). It is speculated that the introduction of carboxylation reduces the crystallinity of PVA, increases the degradation rate, and makes the product more easily degradable.
[0093] (3) Liquid absorption test
[0094] The nasal hemostatic filling materials prepared in Examples 1-5 and Comparative Examples 1-6 were cut into small cubes of 5 mm × 5 mm × 5 mm, and the liquid absorption test was measured according to YY / T 1511-2017 6.3, where m1 is the initial test mass and m2 is the mass after liquid absorption; at the same time, the final volume V was measured, and the volume expansion rate and water absorption rate were calculated.
[0095] Volume expansion ratio = V / 125mm 3
[0096] Water absorption ratio = (m2-m1) / m1
[0097] The results are shown in Table 1 below. By comparison, it can be seen that the higher the CPVA content, the better the liquid absorption effect of the nasal hemostatic filling material, and the greater the product expansion multiple, while the same CPVA content, high carboxylation degree, low water absorption rate, small expansion multiple. The higher the content of PL, PL-CDs / RHC or RHC in the component, the higher the degree of cross-linking, which also reduces the liquid absorption rate and volume expansion rate of the product.
[0098] (4) Antibacterial test
[0099] In vitro antibacterial experiments were performed to evaluate the antibacterial effects of the nasal hemostatic packing materials of Examples 1-5 and Comparative Examples 1-6 on pathogenic Staphylococcus aureus.
[0100] First, the original Staphylococcus aureus culture was diluted step by step with LB liquid medium to obtain 10 7 CFU / mL of fresh bacterial liquid. Take 0.1mL of bacterial liquid and evenly spread it on the entire agar medium surface with a coating stick. After the water on the plane is completely absorbed by the agar, use sterile tweezers to place the sterilized nasal hemostatic sponge on the solid culture medium plate, with the center of the sample at least 15mm away from the edge. Then place it in a 37℃ constant temperature incubator for 24h, observe the range of the inhibition zone, and evaluate the antibacterial properties of the nasal hemostatic filling material.
[0101] The results are as follows Figure 2-4 The effect diagram of the antibacterial experiment on Staphylococcus aureus shows that, by observing Example 1, Example 2, Example 3, Example 5, and Comparative Examples 1-6, inhibition zones can be observed except for Comparative Example 1. The inhibition zones of the comparative examples are smaller, while Examples 1 and 2 have larger inhibition zones, indicating that the introduction of PL-CDs increases the antibacterial property of the nasal hemostatic filling material.
[0102] (5) Mechanical properties test
[0103] Method: Cut the products of Examples 1-5 and Comparative Examples 1-6 into strip specimens with a width of 1 mm, clamp the two ends of the product with a clamp, and use an electronic universal testing machine to test the mechanical properties, and stretch them at a speed of 100 mm / min.
[0104] The results are shown in Table 1. Increasing the amount of AA will increase the degree of carboxylation and reduce the mechanical properties of the product. However, increasing one or more of PL, PL-CDs, and RHC will increase the degree of crosslinking, reduce the water absorption of the product, and improve the mechanical properties.
[0105] Table 1 Performance characteristics of nasal hemostatic filling materials
[0106]
[0107] (6) Hemostasis experiment: Before hemostasis, the samples of Examples 1, 4 and Comparative Examples 5 and 6, the commercially available nasal hemostatic sponge (mainly composed of PVA), and the commercially available collagen sponge (mainly composed of collagen) were prepared into blocks of 20 mm × 20 mm × 5 mm and sterilized by ultraviolet irradiation. A New Zealand white rabbit was fixed with a surgical frame, and the rabbit ear artery was disinfected with iodine tincture, and then the rabbit was anesthetized by injection of xylazine hydrochloride solution (30 mg / kg). The rabbit ear artery was cut at 7 cm from the ear artery, and the incision length was 1 cm. Then, the samples of Examples 1, 4, 5 and Comparative Examples 5 and 6, the PVA sponge and the collagen sponge were placed on the bleeding site and pressurized according to the product expansion effect, and the hemostasis time was recorded.
[0108] The results are as follows Figure 6 , from Example 1, Example 4, and Comparative Example 5, as the proportion of RHC solution increases, the hemostatic effect of the product is better, and the addition of RHC can improve the hemostatic effect of the product, and is better than the PVA sponge and collagen sponge on the market. By comparing Example 1 and Comparative Example 6, the PL-CDs / RHC ratio is too high, the expansion rate of the material is low, and the hemostatic effect of the sample is reduced. The ultimate hemostatic effect of the product is related to the RHC content and CPVA content.
[0109] It should be noted that the above examples are only used to illustrate the technical solution of the present embodiment and are not intended to limit it. Although the present embodiment is described in detail with reference to the given examples, a person of ordinary skill in the art may modify or replace the technical solution of the present embodiment as required without departing from the spirit and scope of the technical solution of the present embodiment.
Claims
1. A nasal hemostatic filling material, characterized in that: The hemostatic filling material is a composite material formed by epsilon-polylysine carbon dots (PL-CDs) / humanized collagen (RHC), epsilon-polylysine (PL) and carboxylated polyvinyl alcohol (CPVA) copolymer.
2. The nasal hemostatic filling material according to claim 1, characterized in that: The ε-polylysine carbon dots are prepared by using ε-polylysine as a carbon source to obtain carbon quantum dots. Specifically, the preparation method is as follows: ε-polylysine is placed in a high temperature environment for pyrolysis treatment, and then crushed and purified to obtain the carbon dots; Furthermore, the average molecular weight of the ε-polylysine is 1000-10000; The specific conditions of the pyrolysis treatment are: treating at 200-300°C for 0.5-5 hours, and then keeping warm for 1-10 hours; Further, the cooled pyrolysis product is soaked in water, the water-insoluble solid is separated and ground, placed in water for ultrasonic treatment, centrifuged to obtain the supernatant, the supernatant is mixed with the remaining pyrolysis product soaking water for dialysis, and freeze-dried to obtain; Wherein, the specific conditions of the dialysis are: the molecular weight cut-off is 1000-10000; The specific conditions for freeze-drying are: pre-freezing at -20°C for 24 hours, rapid freezing at -80°C for 12 hours, and freeze-drying at -20°C for 24 hours.
3. The nasal hemostatic filling material according to claim 1, characterized in that: The carboxylated polyvinyl alcohol copolymer is prepared by the following method: Vinyl acetate is added to methanol, and under inert gas conditions, azobisisobutyronitrile and acrylic acid are added to carry out copolymerization reaction to obtain the intermediate product P(VAc-co-AA); then P(VAc-co-AA) is redissolved in methanol, and sodium hydroxide methanol solution is added to carry out alcoholysis to obtain a gel-like product, which is purified to obtain CPVA.
4. The nasal hemostatic filling material according to claim 3, characterized in that: The inert gas is nitrogen; The mass ratio of vinyl acetate, azobisisobutyronitrile and acrylic acid is 10-20:001-0.1:0.1-1, and the specific conditions of the copolymerization reaction are: reacting at 50-80° C. for 1-20 hours.
5. The method for preparing the nasal hemostatic filling material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1, mixing the ε-polylysine carbon dot solution with the humanized collagen solution to obtain a PL-CDs / RHC mixed solution; S2. Add EDC and NHS to the carboxylated polyvinyl alcohol copolymer solution for activation treatment, dry and redissolve, then add ε-polylysine and PL-CDs / RHC mixed solution, stir evenly for reaction, dialyze and freeze-dry to obtain the product.
6. The preparation method according to claim 5, characterized in that: In the step S1, the mass fraction of the ε-polylysine carbon dot solution is 5-15% (w / v); the solvent is water; The mass fraction of the humanized collagen solution is 1-5% (w / v).
7. The preparation method according to claim 5, characterized in that: In the step S2, the mass fraction of the carboxylated polyvinyl alcohol copolymer solution is 1-10% (w / v); the solvent of the carboxylated polyvinyl alcohol copolymer solution is anhydrous ethanol or dichloromethane; The molar ratio of CPVA to EDC and NHS is 5-20:0.5-5:0.1-1; The specific conditions for drying and re-dissolving are: drying at 50-70° C. to precipitate solids, and then adding water for re-dissolving; the mass volume ratio of the carboxylated polyvinyl alcohol copolymer to water is 0.5-2:15-25 (g / mL).
8. The preparation method according to claim 5, characterized in that: In step S2, the solute mass ratio of PL-CDs / RHC:CPVA:PL is 1-10:0.5-2:0.5-2; The specific reaction conditions are: react at 20-40°C for 1-20h.
9. Use of the nasal hemostatic filling material according to any one of claims 1 to 4 in the preparation of nasal hemostatic filling products.
10. A nasal hemostatic filling product, characterized in that: The product at least comprises the nasal hemostatic filling material according to any one of claims 1 to 4; further, the product is a medical device.
